Integrando lingüística de corpus e aprendizagem experiencial: uma proposta de atividade de ensino com conteúdo multimídia veiculado on-line - Morales, Flavia Priscila de Oliveira (2008)
The main objective of this research is to propose activities for English classes, by making use of on-line multimedia content and concordances. In order to achieve such purpose, we followed the Corpus Linguistics theoretical and methodological frameworks, and also the teaching and learning theory presented by the Experiential Learning (Kolb,1989; Nunan, 1992; Kohonen, 2002). we see concordances as the main tool to be applied in a teaching corpus (Berber Sardinha, 2004:272), since we comply with the Corpus Linguistics and teaching research basis which were already proposed by several authors (Johns, 1994; Fox, 1998; Sinclair, 2003; Richards, 2001; Tomlinson, 2003). However, we have realized that activities, which are solely focused on concordances, can be seen as out of context, repetitive and uninteresting. Therefore, considering the present availability of on-line resources provided to our society, the use of multimedia content as a motivating factor to teach languages seems to offer a good alternative in order to find viable solutions to such problems. we highlighted one of the main concepts advocated by Corpus Linguistics that considers language as a probabilistic system that presents a certain regularity in the types of association to which the words of a language are submitted to (Berber Sardinha, 2004:39). Following the Experiential Learning Theory, we understand that theoretical concepts will be part of one s reference only when s/he has experienced them in a meaningful way, at an emotional level. The use of multimedia content can also contribute to this conception. Two corpora were used in this investigation: the first is a research corpus comprising speech transcripts from films and real contexts totaling 335,498 tokens; and the second is the reference corpus built from the BNC (British National Corpus) spoken part, with a total of 11,063,472 tokens. Linguistic content was extracted from the research corpus so as to propose the teaching activities presented here. Therefore, the research questions are related to aspects of the typical linguistic features found in the research corpus. we hope that this research will contribute to the pedagogical practice of English teachers who are willing to use corpus in their classes. we also believe that it might fill in a gap found in previous research concerning the use of multimedia content available on-line. we hope that this research will help to integrate the Corpus Linguistics empirical view to the Experiential Learning theory as well